THE IMPORTANCE OF ONLINE SHOPPING BASED ON SHARIA ECONOMIC PRINCIPLES: A REVIEW OF DSN-MUI FATWA - Chudriana Putri, Rafika (Proceeding International Seminar of Islamic Studies, 2023)
At the end of 2019, the whole world, including Indonesia, has experienced a disaster in the form of a plague or virus that infects humans. This event is the beginning of human economic activities starting to change. Technology began to place the top position as an alternative in world economic activities to implement social distancing. If in the past buying and selling could only be done in person, now it switches to online buying and selling without having to meet face to face so that it is more practical. As an Indonesian society with an Islamic majority, in the face of changes in economic activity like this, it raises questions for the community about how to buy and sell online according to sharia guidelines. So that the urgency of the Sharia Economic Fatwa, especially regarding online shops based on sharia principles, is important to discuss. This research method is descriptive research, namely by describing a research result. Researchers also use literature studies by studying reading materials related to the problems in the journal. The result is that with the issuance of the DSN-MUI fatwa on online shops based on sharia principles to conduct contract transactions through electronic media, it will open up business opportunities for the progress and development of the Indonesian economy.